Knowledge and Attitudes Regardlng Use of Insulin among Diabetic Patients in Selected Hospitals in Colombo District - Wijesinghe, D.S.; Pathirana, R.L.; Perera, P.P.R. (Proceedings of the 2nd International Conference on Public Health (ICOPH 2016), 2016)
Attached

For better glycemic control and adherence to Insulin therapy, improvement in knowledge and attitudes regarding Insulin use can be effectively used. The study was conducted to assess the level of knowledge and attitudes regarding Insulin use among diabetic patients. A descriptive cross sectional study was carried out among diabetic patients, aged 18 years and above who were on Insulin, attending diabetic or medical clinics in selected five hospitals in Colombo district. For collecting data a pretested, interviewer administered, structured questionnaire was used. Out of the total 400 respondents, more than half (63.8%) knew why they were on Insulin. Only 36.2% study subjects knew at least three symptoms of hypoglycemia. From the total population only 17.8% knew the purpose of doing HbAlc test. Nearly half of the study subjects (52.0%) believed that Insulin does not cause harm to them. From the respondents 61.5% thought that there is no substitution for Insulin while 76.8% believed that bitter condiments have an effect on lowering blood sugar. The majority of the total population (87.3%) had an opinion that they would stop Insulin if they were given a chance. Knowledge and attitudes regarding Insulin therapy were favorable in some questioned areas but could not be satisfied in certain critical areas such as awareness of HbAlc test. Therefore initial and continuous patient education and motivation are necessary for achieving therapeutic goals of the Insulin therapy.
Keywords: insulin therapy